THE PROBLEM OF HEALTH PROTECTION IN MODERN EDUCATIONAL INSTITUTIONS - Smolinska, Olesia; Budnyk, Olena; Voitovych, Anna; Palahniuk, Mykhailo; Smoliuk, Artem (Revista Inclusiones, 2020)
Preserving young people’ health is an important task of the world community, especially during today’s global spread of dangerous infections (in particular, the coronavirus pandemic), stressful situations and conflicts, bulling and cyberbullying, financial, economic and social instability, etc. The purpose of the article is to make the analysis of theoretical aspects of preserving physical, mental, social and spiritual students’ health in educational institutions, as well as the results of our empirical research of this problem.